Individual - Medication Safety Box (I-MEDS BOX) / Norimah Said … [et al.] - Said, Norimah; Nordin, Roswati; Mohammad, Norfidah; Abdul Razak, Hairil Rasmizal; Said, Nur Shahrina (Research Innovation Business Unit, 2014)
I-MEDS Box (Individual Medication Safety Box) Medication errors are common types of medical errors that occur in health care institutions. It affects health care institutions and adversely affects the patient’s quality of life. This involves professional practice, health care products, procedure and system, prescribing, order communication, product labelling, packaging and distribution, administration, education, monitoring and use. Before administration of the medication, a nurse should verify the medication prescribed by the doctor first. The administration of medicine is to ensure that patient gains the clinical benefit and ensures that they do not suffer from any adverse effects of their medication. The procedure in administering the medication is the nurses have to check the patient’s allergy first, read the medication chart or prescription carefully and ensure the prescription and the dispensed medicine is clearly written and unambiguous. A nurse also has to check that the medication is correct for the patient, ensure that the prescribed dose has not been given already, select the medicine required, check against the prescription, and check the expiry date and identity of the patient. This shows that the nurses require a variety of skills during administering medications, and assisting other health personnel administers medications. The objective of this innovative is to develop I-MEDS Box (Individual Medication Safety Box) tool in serving medication for patients during hospitalization and to improve workflow of administering medication to patients. Therefore, with I-MEDS Box it will reduce the workload of nurses which will indirectly reduce the time spent on handling and managing the medication trolley. Currently, in clinical setting nurses are using medication trolleys for administration of medication. Nevertheless, the expected outcomes of this I-MEDS Box tool is to prevent errors, improve medication safety with individual medication box, to eliminate delays due medication availability, missing doses, and time-consuming controlled substance counts and ensure pharmacist review of orders prior to administration in ward. I-MEDS Box also includes an electronic system with controlling temperature and alarm system. The I-MEDS Box has a security system using security card to access. There are four compartments to keep the different medication such as tablet form, injection and mixture form. In conclusion, I-MEDS Box also includes a method of controlling and securely dispensing pharmaceutical items and storing pharmaceutical items in a ward.